The Resistance of Javanese and Sundanese Cultural Identities in Indonesian Magical-Realism Novel into English - Nadia Khumairo Ma'shumah; Sajarwa Sajarwa (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Identity is also at the core of the translation project. Thus, the translator's role as a mediator between different languages and cultures cannot be isolated from efforts to harmonize the building of identity and cultural knowledge. This study investigates how the translator preserves the source text's cultural identity in the target text, based on evidence that the translation process is likewise a cultural transfer. The frameworks for this study were Venuti's idea of "resistancy", Newmark's cultural terms categorizations, Baker's techniques for specific-culture items, and Newmark's transposition procedure. The material objects of this research were the Indonesian magical-realism novel 'Cantik Itu Luka' and its English translation ‘Beauty is A Wound’. By employing descriptive-qualitative approach, a thorough investigation of this study revealed that the translator tends to challenge the target readers’ knowledge by preserving the source text's identity in the target text. To do so, the translator frequently uses loan words and the application of blended strategies, such as loan words with superordinate (a more general word), loan words with explanation (couplets), and loan words with transposition and explanation strategies (triplets).